Cultural competence in America's schools : leadership, engagement and understanding - Nichols, Edwin J. (Educational policy in the 21st century., 2013)
"Focuses on explicating the impact of culture and issues of race and ethnicity on student learning, teacher and leadership efficacy, and educational policy making in our nation's public school system."--Page 4 of cover.